Bio-mediated synthesis of monodisperse hematite nanoparticles from pyrite - Mchibwa, Kudzai Angeline (My University, 2010)
Acidianus spp. a thermophilic bacteria which can oxidize sulphide minerals was used to oxidize pyrite, FeS2 resulting in the production of acidic ferric sulphate solutions. The ferric sulphate solutions were aged through a forced hydrolysis process at different pH conditions to yield a variety of iron oxide and basic sulphate precipitates. The precipitates were characterized by XRD, SEM and BET analysis. Potassium jarosite was formed as the main phase under acidic conditions whilst maghemite - Fe2O3was precipitated as the main phase at a pH of 6-7. Magnetite Fe3O4 was formed as the main phase at a pH of 7-8 as well as a pH of 8-9. Spherical globular aggregates of magnetite nanoparticles of high purity and a surface area of 20.77m2/g were precipitated at a pH of 7-8. Hematite -Fe2O3 nanoparticles were then produced via an oxidative transformation of the precursor magnetite nanoparticles at 600°C. The spherical hematite nanoparticles had a surface area of 18.69m2/g and a pore volume of 0.0698cm3/g. This process can thus provide a cheaper alternative for the production of hematite nanoparticles. Hematite nanoparticles have a wide range of uses in fields such as electronics, optics and biomedicine. The findings can be used in acid mine drainage treatment and other systems where iron removal is problematic.